179k views
2 votes
Evaluate 6(5-(6-5)-3​

User Spikatrix
by
5.1k points

2 Answers

2 votes

Answer:

The correct answer for 6(5 - (6 - 5) - 3 would be 6.

Explanation:

6(5 - (6 - 5) - 3)

= 6(5 - 1 - 3)

=6(4 - 3)

=(6)(1)

= 6

Hope this helps!

User Daniel Kereama
by
5.4k points
1 vote

Answer:

Explanation:

Evaluate 6(5-(6-5)-3​) = 6(5-1-3​) {first solve innermost bracket}

= 6* (5-4) = 6*1 =6

User Roderick Obrist
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.